Abusive supervision, co-worker abuse and work outcomes: procedural justice as a mediator. Issue 3 (12th September 2019) - Ramdeo, Shalini; Singh, Riann
Abstract : Purpose: Based on the social exchange theory and the reactance theory, the purpose of this paper is to investigate the effects of workplace abuse from two sources. The study explores the linkage between abusive supervision and co-worker abuse on the targeted employee's organizational commitment, organizational citizenship behavior and intention to quit as mediated by procedural justice. Furthermore, this study extends understanding workplace abuse consequences by investigating its effects on organizational citizenship behavior directed to individuals and organizational citizenship behavior directed to the organization. Design/methodology/approach: To test the proposed hypotheses, a cross-sectional research design was used. The sample comprised 500 employees working in various private and public sector organizations in the Republic of Trinidad and Tobago. Using a split-sample approach, mediation analyses were performed on the test and validation samples. Findings: The research results showed that procedural justice mediated the relationship between abusive supervision and affective and normative commitment, organizational citizenship behavior directed to individuals and intention to quit. Procedural justice was found to mediate the relationship between co-worker abuse and affective and normative commitment, and intention to quit. Originality/value: This study extends previous academic studies on workplace abuse by comparing the effects of abusive supervision and the lesser researched source of co-worker abuse on the targeted employee's organizational commitment, organizational citizenship behavior and intention to quit. It also reports on the effects of each source on an employee's organizational citizenship behavior directed to individuals and organizational citizenship behavior directed to the organization, as there is limited empirical research within the workplace abuse literate on these two dimensions.